Penerapan Vector Error Correction Model Pada Variabel Makro Ekonomi Di Indonesia - Moh. Faizin (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
In this time, the countries can be said to be in a good condition of the national economy if there are some indicators in positive economic macro, it is including the decline of inflation, the amount of money circulating is also declined, and the exchange rate strengthening against foreign currencies and reduced interest rates. The purpose of this study is to analyze the causality and cointegration relationships of economic macro variables, by using time series data for 2010-2019 and using the VECM model. The results of the study found that there is no causal relationship between inflation and the BI rate. Likewise, the variable money supply does not affect the BI rate. The exchange rate also does not affect each other on the BI rate variable. Causality test results also indicate that the money supply does not have a causality relationship to inflation, while the exchange rate variables influence each other on inflation. To exchange rates, it does not give affect in the variable amount of money in circulation each other. By explanation of the estimation results of the VECM model, it shows the long-term and short-term relationships of each variable generally.